2014
DOI: 10.1515/ijnes-2013-0020
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Survival: Fostering Growth and Innovation in Doctoral Study – A Concept Analysis of the Ba Space

Abstract: AbstractPurpose: This concept analysis examines the Ba space in the context of interdisciplinary doctoral study in nursing and healthcare innovation in a minimal residency program. The authors identified Ba in their small, highly diverse, self-selected doctoral study group and believe Ba is an educational innovation that will prove useful to nursing and healthcare educators.Background: Ba originates from Japanese ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It is about the here-and-now and thrives on people with different viewpoints 4849 50. It has four characteristics: originating (face-to-face, individual communications), interacting (face-to-face group dialogue), cyber (virtual group interactions) and exercising (virtual individual interactions) 50.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is about the here-and-now and thrives on people with different viewpoints 4849 50. It has four characteristics: originating (face-to-face, individual communications), interacting (face-to-face group dialogue), cyber (virtual group interactions) and exercising (virtual individual interactions) 50.…”
Section: Discussionmentioning
confidence: 99%
“…Ba space occurs naturally, is not prescribed, relationships are fluid, permeable and iterative 49 50. It has four characteristics: originating (face-to-face, individual communications), interacting (face-to-face group dialogue), cyber (virtual group interactions) and exercising (virtual individual interactions) 50. In the main Ba has been considered in business organisations 51–56.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharing this explicit knowledge will form new tacit knowledge for each person involved. Although the process considers each individual involved, a very important factor about it is that it continuously involves the sharing of group knowledge, which ‘results in a transcendence or connection between individuals' ( 62 ). The socialization step of the model in particular, require the mutual participation of all persons involved ( 63 ), therefore fostering co-operation and relationships with others.…”
Section: The Seci Model Ba and Person-centerednessmentioning
confidence: 99%
“…Finally, exercising ba mainly offers a context for active and continuous individual learning and corresponds to the internalization step. Krahe et al (2014) identified ba space in doctoral studies of nursing and healthcare innovation. They believe ba will bring educational innovation for nursing and healthcare educators.…”
Section: Literature Knowledge Types and Knowledge Creationmentioning
confidence: 99%